Assessment of Iron Burden and Siderosis-related Complications in Patients with Transfusion-dependent Thalassaemia - Karniza Khalid; Nordiyana Azmi; Irma Liyana Mushaddik; Ahmad Afnan Mohamad Puad; Siti Akma Ishak (Research Highlights in Disease and Health Research Vol. 8, 2023)
Objective: Herein, we aim to assess the iron burden and siderosis-related complications among patients with transfusion-dependent thalassaemia (TDT). We also aim to explore the value of cardiac T2* magnetic resonance (MR) to predict potential cardiac complications among patients with TDT. Methods: We performed a cross-sectional study reviewing medical records of 75 TDT patients in Hospital Tuanku Fauziah, Perlis, Malaysia. A total of 151 reports from magnetic resonance (MR) T2* performed from 1 January 2015 till 31 December 2021 were transcribed together with relevant biochemical markers and echocardiogram results that were performed within the same calendar year. Results: We found a moderate correlation between serum ferritin and myocardial (r=0.356, p<0.001), and liver iron loading (r=0.572, p<0.001). There was a moderate correlation between serum ferritin and serum ALT (r=0.462, p<0.001), AST (r=0.465, p<0.001), magnesium (p=-0.276, p=0.002) and phosphate (r=-0.221, p=0.014). All patients had normal ejection fraction, 43 (28.5%) had raised pulmonary artery pressure and none had evidence of diastolic dysfunction. There was no predictive variable to predict cardiac complications among our pool of TDT patients. Conclusion: The significant correlation between serum ferritin and myocardial/liver iron loading should prompt effective chelation strategy to prevent clinical complications among patients with TDT.